Learning to use AutoCAD 3D - Leake, James; Autodesk Press (Clifton Park, N.Y. : Autodesk Press, 2003)
Instruction and tutorial disc for autoCAD 3D. The disc contain several lessons, quizzes, examples and learning aids.
System requirement: Windows 95, 98, ME, NT4, or XP Home or Professional resolution of 800 x 600 or higher ; color depth of 16 bit or higher 8x cd-rom or higher, 32MB of RAM or more.
Keywords: Computer graphics; Computer-aided design